2023
DOI: 10.1108/gs-10-2022-0107
|View full text |Cite
|
Sign up to set email alerts
|

Grey forecast of electricity production from coal and renewable sources in the USA, Japan and China

Abstract: PurposeElectricity plays an essential role in nations' economic development. However, coal and renewables currently play an important part in electricity production in major world economies. The current study aims to forecast the electricity production from coal and renewables in the USA, China and Japan.Design/methodology/approachTwo intelligent grey forecasting models – optimized discrete grey forecasting model DGM (1,1,α), and optimized even grey forecasting model EGM (1,1,α,θ) – are used to forecast electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…< 10 [10, 20) [20, 30) ≥ 30 𝐻𝑖𝑔ℎ𝑙𝑦 𝑎𝑐𝑐𝑢𝑟𝑎𝑡𝑒 𝑓𝑜𝑟𝑒𝑐𝑎𝑠𝑡 𝐺𝑜𝑜𝑑 𝑓𝑜𝑟𝑒𝑐𝑎𝑠𝑡 𝑅𝑒𝑎𝑠𝑜𝑛𝑎𝑏𝑙𝑒 𝑓𝑜𝑟𝑒𝑐𝑎𝑠𝑡 𝐼𝑛𝑎𝑐𝑐𝑢𝑟𝑎𝑡𝑒 𝑓𝑜𝑟𝑒𝑐𝑎𝑠𝑡 Literature (Gowrisankar et al, 2022;Tulkinov, 2023) has confirmed the rationality and validity of the revised scale. The scale does not represent absolute truth, and a user may adjust it depending on the sensitivity of the forecasting problem.…”
Section: 𝑀𝐴𝑃𝐸(%) = {mentioning
confidence: 85%
See 1 more Smart Citation
“…< 10 [10, 20) [20, 30) ≥ 30 𝐻𝑖𝑔ℎ𝑙𝑦 𝑎𝑐𝑐𝑢𝑟𝑎𝑡𝑒 𝑓𝑜𝑟𝑒𝑐𝑎𝑠𝑡 𝐺𝑜𝑜𝑑 𝑓𝑜𝑟𝑒𝑐𝑎𝑠𝑡 𝑅𝑒𝑎𝑠𝑜𝑛𝑎𝑏𝑙𝑒 𝑓𝑜𝑟𝑒𝑐𝑎𝑠𝑡 𝐼𝑛𝑎𝑐𝑐𝑢𝑟𝑎𝑡𝑒 𝑓𝑜𝑟𝑒𝑐𝑎𝑠𝑡 Literature (Gowrisankar et al, 2022;Tulkinov, 2023) has confirmed the rationality and validity of the revised scale. The scale does not represent absolute truth, and a user may adjust it depending on the sensitivity of the forecasting problem.…”
Section: 𝑀𝐴𝑃𝐸(%) = {mentioning
confidence: 85%
“…EGM (1, 1, 𝛼, 𝜃) represents the even form of a grey model with a first-order differential equation containing one variable and weighted background value involving conformable fractional accumulation. It was proposed by Javed et al (2020), and has seen several interesting applications (see, e.g., Tulkinov, 2023;Podrecca & Sartor, 2023;Singh et al, 2022). Let the set of actual data is 𝑋 (0) = (𝑥 (0) (1), 𝑥 (0) (2), … 𝑥 (0) (𝑛)) , 𝑥 (0) (𝑘) ≥ 0, 𝑛 ≥ 4…”
Section: Egm (1 1 α θ)mentioning
confidence: 99%
“…It has been more than 40 years since grey system theory was first proposed by Professor Deng in 1982 (Deng, 1982), and it is now widely used in many fields such as agriculture, industry, water conservancy, economy and energy (Luo and Li, 2023;Tulkinov, 2023;Zhao et al, 2023;Hu, 2023). The Grey Forecasting Theory, as the core system of grey system theory, has achieved a series of important findings after years of research and development (Zhang et al, 2023;Sapnken, 2023;Li et al, 2023a;Wei et al, 2023).…”
Section: Introductionmentioning
confidence: 99%